Analysis of Personality Competencies of Islamic Religious Education Teachers in Forming Discipline at SMP Negeri 14 Sarolangun - Salman Alparisi; Jaya Jaya (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the personality competence of Islamic Religious Education (PAI) teachers in shaping student discipline at SMP Negeri 14 Sarolangun. The method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation involving PAI teachers and students. The results of the study indicate that the personality competence of PAI teachers is categorized as very good, as demonstrated through firm, stable, wise, and authoritative attitudes. PAI teachers serve as uswah hasanah (role models) in internalizing discipline values through habituation to worship and compliance with school rules. Although there are external obstacles such as lack of family environment control and social media influence, the exemplary personality of teachers is proven effective in increasing students' discipline awareness. In conclusion, teachers' personality competence is a crucial instrument in the successful formation of discipline character in junior high schools.